Effect of surface profiling on the mechanical properties and bond behaviour of mineral-impregnated, carbon-fibre (MCF) reinforcement based on geopolymer. (27th February 2023) - Zhao, Jitong; Liebscher, Marco; Schneider, Kai; Junger, Dominik; Mechtcherine, Viktor
Highlights: Mineral-impregnated carbon-fibre (MCF) produced and profiled continuously. Mechanical and microstructural features influenced by surface geometrical features. Bond properties enhanced by the applied surface profiling. Mechanical properties of MCFs obtained in the ranges of conventional CFRP. Abstract: Mineral-impregnated, carbon-fibre composites (MCF) are a new and promising reinforcement type to become substitutes for conventional steel reinforcements or fibre-reinforced polymers. To enhance this reinforcement's shape stability and load transfer capability to concrete matrices, a surface profiling of this novel material needs to be developed. To this end the automatic, auxiliary helical winding of a thread was implemented to produce semi-finished MCF based on geopolymer (GP) with defined geometrical features. Subsequently, a rapid solidification process was conducted by means of thermally activated geopolymerization of various durations. The results showed that applied surface profiling densified the matrix microstructure of the MCFs and improved shape stability during processing. However, flexural and tensile properties were slightly negatively impaired due to the stress concentrations induced. Furthermore, curing prolonged from 2 to 8 h enhanced the geopolymerization of the matrix gradually and therewith the mechanical performance of the MCFs in their entirety, as confirmed by morphological investigation. Uniaxial tension tests demonstrated that the strengths of all rod variants were in the same range as that of conventional CFRP. Enhanced bond properties were found for MCF with the profiling technology as developed, enabling defined load-bearing behaviour for subsequent application.